Genetic improvement of banana for resistance to xanthomonas wilt in East Africa - Musabyemungu, A.; Tripathi, J.; Muiruri, K.S.; Gaidashova, S.; Rukundo, P.; Tripathi, L. (2025)
Banana (Musa spp.) is a staple food and income generation crop, feeding millions worldwide. However, the cultivation of bananas is challenging due to biotic and abiotic production constraints. Among these factors are pests and diseases, especially banana bacterial disease. Banana Xanthomonas wilt (BXW), caused by Xanthomonas campestris pathovar musacearum (Xcm), has the most significant detrimental economic effect on East African banana production. The infection of BXW is rapid and severe; its impact increases over time and causes huge banana yield losses. The Xcm infects and causes disease in all types of bananas except the wild diploid type Musa balbisiana, which is resistant boosting plant immunity for controlling Xcm and other diseases in bananas. Resistant cultivars are the best promising management option for controlling Xcm and other diseases in bananas. All the cultivated bananas are sterile, and have a long generation cycle, which complicates their improvement through conventional breeding. Biotechnological approaches to banana improvement can complement conventional breeding by overcoming some of its challenges. Additionally, genetic engineering could speed up the process of crop improvement, especially for sterile seedless crops like bananas. It is also specific to the target gene and precise modification that avoids unwanted genes in the normal breeding process. Recent developments using genetic engineering and genome editing on bananas have been initiated to tackle these issues. This review article focuses on the challenges of traditional breeding and the progress of genetic engineering and genome editing approaches, aiming to enhance understanding of achieving an essential genetic gain of bananas against the BXW. This understanding is crucial for enhancing food security in East Africa and globally.